Explaining preferences for illustration style and characteristics in early childhood - Županić Benić, Marijana; Kalić, Kristina (Revija za elementarno izobraževanje, 2019)
The purpose of this study was to explore how children perceive the style and characteristics of illustrations in picture books. It was found that six-year-old children preferred expressionist and surrealist illustrations, whereas four-year-old children preferred expressionist and romantic illustrations. They liked illustrations mostly because they were colorful, but also because they saw familiar motifs and actions in those illustrations. Children are also likely to prefer illustrations that are textile-shaped, illustrations that resemble children’s drawings, and naive, happy illustrations. These findings are consistent with previous studies of children’s preferences for illustrations and serve as a reference point for future studies.
Keywords: artistic styles; ilustration characteristics; picture book; preschool child